Marketing interno para el incremento de la productividad en la logística de la Distribuidora Farmacéutica Ecuatoriana - Holguín Padilla, Andrés Alejandro (2020)
The main objective of this research work is to increase the productivity in the logistics of the Ecuadorian Pharmaceutical Distributor, through the implementation of internal marketing strategies. Chapter in which we define the dependent and independent variables resulting from the survey of a market through the survey that defines the problem or need to be treated. In the second chapter, mention the concepts related to the topics to be treated together with the key words and theories to follow everything covered in a legal and referential scope…………